2006
DOI: 10.1093/jxb/erl201
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of an Arabidopsis magnesium transport gene, AtMGT1, in Nicotiana benthamiana confers Al tolerance

Abstract: Aluminium (Al) toxicity is the most important limiting factor for crop production in acid soil environments worldwide. In some plant species, application of magnesium (Mg(2+)) can alleviate Al toxicity. However, it remains unknown whether overexpression of magnesium transport proteins can improve Al tolerance. Here, the role of AtMGT1, a member of the Arabidopsis magnesium transport family involved in Mg(2+) transport, played in Al tolerance in higher plants was investigated. Expression of 35S::AtMGT1 led to v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(61 citation statements)
references
References 48 publications
1
60
0
Order By: Relevance
“…This phenomenon is not yet fully understood. However, from the available information it may be concluded that the observed competition for uptake is a consequence of the lack of specificity of the individual uptake systems for each cation (Gardner 2003;Shaul 2002;Deng et al 2006;Marschner 2012). Some Mg transporters may also transport other cations like K. As a consequence a high plant available K concentration in the soil/rhizosphere blocks these unspecific Mg transporters for Mg uptake.…”
Section: Mechanisms Of Mg Uptake By Cropsmentioning
confidence: 99%
“…This phenomenon is not yet fully understood. However, from the available information it may be concluded that the observed competition for uptake is a consequence of the lack of specificity of the individual uptake systems for each cation (Gardner 2003;Shaul 2002;Deng et al 2006;Marschner 2012). Some Mg transporters may also transport other cations like K. As a consequence a high plant available K concentration in the soil/rhizosphere blocks these unspecific Mg transporters for Mg uptake.…”
Section: Mechanisms Of Mg Uptake By Cropsmentioning
confidence: 99%
“…This Al-induced Mg deficiency has been suggested as a primary cause of Al toxicity (MacDiarmid & Gardner, 1996). Support for this hypothesis comes from research where overexpression of yeast and bacterial Mg transporters in yeast increased Mg (Co 2+ ) uptake and improved Al tolerance significantly (Fowler et al, 1999) and the more recent findings that overexpression of an Arabidopsis magnesium transport gene in Nicotiana benthamiana increased Mg uptake in the presence of Al and conferred Al tolerance (Deng et al, 2006).…”
Section: Protective Effect Of Magnesium On Distinct Root Classes Of 1mentioning
confidence: 96%
“…MacDiarmid & Gardner (1996) also reported that the toxic effect of Al 3+ on Sacharomyces cerevisae was mitigated by Mg supplementation, unlike similar additions of Ca to the growth medium. Furthermore, it was recently reported that the overexpression of an Arabidopsis magnesium transport gene in Nicotiana benthamiana increased Mg uptake in the presence of Al and conferred Al tolerance (Deng et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…AtMGT2-10/AtMGT1 functionally complemented a bacterial mutant lacking Mg transport capability and was localized to the plasma membrane (Li et al 2001). Overexpression of AtMGT2-10/AtMGT1 was found to contribute to tolerance to low levels of Mg in external solution (Deng et al 2006). One other gene, AtMHX, has been identified as a vacuolar Mg 2þ /H þ exchanger in Arabidopsis: mRNA of AtMHX is highly accumulated at the xylem parenchyma where the cells may play a key role in xylem loading and unloading (Shaul et al 1999).…”
Section: Introductionmentioning
confidence: 99%